Design of minimum water network for global water operation - Wan Muhammad Syahmi, Wan Muhammad (2012)
Water is key utilities in process industry.A reduction of this utility can reduce plant capital as well as operating cost.Though there are graphical techniques that often are use but mathematical modelling techniques can produce global optimal solution which means it best techniques to be used. In this paper,a new systematic design methodology has been developed for the water minimization involving multiple-contaminant systems that also feature maximum re-use water. In this study,the proposed model is developed based on linear programming (LP).The technique consists of four main steps,i.e.limiting water and energy data extraction, superstructure representation, mathematical formulation, and finally,result analysis.This technique is applicable to mass transfer based and non-mass transfer based (global water operations).The proposed methodology is mathematically rigorous and targets the minimum utility requirement satisfying for detailed design of the water allocation network.The model is successfully implemented on in two industrial case studies involving petroleum refinery and chlor-alkali plant.The proposed model also can guarantee the global optimal solution.Through this approach, the optimal design of the water network can be achieved.